Eschar as a Sensitive Marker for Scrub Typhus Diagnosis at the Primary Healthcare Level (Indian Journal of Public Health Research & Development, 2022)
Background and aim of study: Scrub typhus, a potentially fatal rickettsial disease, is reported from many Indianstates, but mostly from tertiary care centers. This study is distinct as it was undertaken in a primary care center ina rural area. Aim was to observe the age, gender and occupational profile of patients diagnosed with scrub typhusat our center during the period from January 2017-19; to find out about the site and day of appearance of escharwith respect to duration of fever and to note the clinical features and complications of scrub typhus.Methods: Study sample consisted of patients presenting with fever who developed an eschar and positive serologyfor Ig M on the 10th day.Conclusion: A total of 31cases were seen, of which four were children and eighteen were adult females. The“eschar” was picked up within 5 days of onset of fever in 26(84%) cases. There was no mortality. This study isunique also in the large size of the cases from a rural center and short latency to effective treatment. The studyemphasizes the necessity of picking up the eschar by detailed examination in all cases of pyrexia and institutingearly specific treatment.
Keywords: eschar, fever, primary health care, scrub typhus